MicroRNAs in HIV-1 infection: an integration of viral and cellular interaction at the genomic level - Tan Gana, Neil H.; Onuki, Tomohiro; Victoriano, Ann Florence B.; Okamoto, Takashi (Frontiers in Microbiology, 2012)
The microRNA pathways govern complex interactions of the host and virus at the transcripts level that regulate cellular responses, viral replication and viral pathogenesis. As a group of single-stranded short non-coding ribonucleotides (ncRNAs), the microRNAs complement their messenger RNA (mRNA) targets to effect post-transcriptional or translational gene silencing. Previous studies showed the ability of human immunodeficiency virus 1 (HIV-1) to encode microRNAs which modify cellular defence mechanisms thus creating an environment favourable for viral invasion and replication. In corollary, cellular microRNAs were linked to the alteration of HIV-1 infection at different stages of replication and latency. As evidences further establish the regulatory involvement of both cellular and viral microRNA in HIV-1-host interactions, there is a necessity to organize this information. This paper would present current and emerging knowledge on these multi-dimensional interactions that may facilitate the design of microRNAs as effective antiretroviral reagents.